Advances in nuclear architecture - Adams, Niall M.; Freemont,Paul S. (Springer eBooks., 2011)
This book provides a snapshot of the state-of-the art in the study of mammalian cell nuclear architecture, and features a diverse range of chapters written by top researchers. A key aspect is an emphasis on precise and repeatable quantitative analysis and simulation in addition to the more familiar biological perspective. The fusion of such material frames the future of the discipline. Quantitative contributions stress reproducible and robust 3D analysis, using a variety of tools ranging from point pattern analysis to shape registration methods. Biological insights include the role of nuclear subdomains in cancer, nuclear molecular motors, and a holistic view of gene transcription.